KEBIJAKAN PEMERINTAH DAERAH DALAM PENGENTASAN KEMISKINAN MELALUI PEMBANGUNAN DAN PENGELOLAAN IRIGASI - Lien Damayanti; Slamet Hartono; Suhatmini Hardyastuti; Dwidjono Hadi Darwanto (Universitas Tadulako, 2011)
In the current era, government has facilitated, trained and supported the implementation ofirrigation development and management providing maximum opportunities to any region, bybringing forward the initiative, capacity, and the regional authority concerned in accordance withthe economic and decentralization spirits. However, based on the present data, it is suggested thatirrigation improvement program has not been able to absolutely alleviate poverty because irrigationis only one of supporting capitals in farming system. The research was conducted in ParigiMoutong from March 2009 to December 2010. Data was collected through survey aimed at: (1)analyzing poverty incidence and gap; (2) identifying government policy on irrigation developmentand management. The research results showed that: (1) based on the poverty incidences and gapanalysis, Torue and South Parigi sub districts had populations of poor people of 55.89 and 49.36%,respectively, (2) the Central Sulawesi governmental policy on Water Resources and IrrigationSector Management Program (WISMP) has been running for 3 years, which is currently a priorityprogram in managing water/irrigation resources. Its implementation is needed in order tosuccesfully create self-supported farmers in participative irrigation management by activelyinvolving water user farmer groups (WUFG) directed to foster the sense of belonging. Thus,responsibility transfer in management can run smoothly and the realization of efficient, effectiveand sustainable irrigation based on self-supported farmer community belong to WUFG isachievable. The WISMP can reduce the poverty level 5% but it was not significant in alleviating povertyKata kunci : Irrigation, poverty, regional government policy.